RESILIENCE AND TRANSFORMATION OF UKRAINIAN EDUCATION IN THE CONTEXT OF WAR AND GLOBAL INTEGRATION - Shamsutdynova, Mariam-Sofiia (SWorld-Ger Conference proceedings, 2025)
This paper analyzes the challenges and resilience of the Ukrainian educational system amid the full-scale war and ongoing systemic issues. Key problems include damaged schools, safety risks, psychological impacts on students, low teacher salaries, outdate